Identification of risk-factors for the development of depressive symptoms in perinatal period: A longitudinal study. (13th April 2021) - Vece, A.; Tarantino, G.; Carfagno, M.; Raia, M.; Ciampi, C.; Vincenzo, M. Di; Pitocco, A.; Sampogna, G.; Luciano, M.; Torella, M.; Fiorillo, A.
Abstract : Introduction: Perinatal depression is a severe and disabling condition, which affects negatively both mothers' and children's mental health and well-being. About 12.8% of pregnant women report depressive symptoms in the perinatal period. Objectives: The aims of the present study are to: 1) identify factors (socio-demographic and clinical) associated with an increased risk of developing PD; 2) promote a screening program on PD. Methods: All pregnant women were assessed at each trimester of pregnancy, three days after the childbirth and after 1, 3, 6 and 12 months, with the Edinburgh Postpartum Depression Scale (EPDS). Women scoring ≥10 on the EPDS were invited to receive a full psychiatric evaluation to confirm the diagnosis. Results: 420 women were recruited. 52.9%, 27.6% and 31.6% of participants presented an EPDS≥ 10 score at The I, II and III trimester of pregnancy, respectively. The percentage of patients with and EPS score ≥19 is 16.6%, 6.8%, 6.8%, 11.3% and 7.8% in 3 days following the childbirth and after 3, 6, 9 and 12 months, respectively. Higher EPDS scores are predicted by the presence of anxiety symptoms before pregnancy and of depressive and anxiety symptoms in previous pregnancies (p<0.05). Women with family conflicts and with anxiety symptoms in the partner are more likely to report higher EPDS scores (p<0.001). Conclusions: Our results confirm that perinatal depression is a highly prevalent condition. An early identification of depressive symptoms during this period is crucial in order to reduce the long-term negative impact on the mothers, the newborn and other family members. Disclosure: No significant relationships.